Utopia - Chan, Wai-May
The allure of "utopia" - a colorful and burstling magical "city" appears short-lived. An accidental blunder on the part of the main character who happened to "walk" into it, provokes outrage of the inhabitants who resort to stonebeating and utlimately expell the intruder.